Guideline for integrating agroecological principles into rapid value chain analyses - Charry, Andres; Narjes, Manuel; Gonzalez, Carolina; Chege, Christine (2024)
CGIAR’s Agroecology Initiative (AE-I) has the objective of testing agroecological approaches across different socioeconomic, political, and geographic contexts, and using the learnings on what agroecological innovations work, where, and for whom, to craft replicable agroecological transition models that can subsequently be applied to the food, land, and water systems of other low- and middle-income countries.